Pathways to Blue Oceans: the case of three agritech companies - Cervantes, Mario José (Kansas State University, 2024)
Blue Ocean Strategy has become the most innovative approach to creating and sustaining competitiveness in organizations. Over the past several years, many organizations across numerous industries have adopted it as a way of ensuring and protecting their performance. The AgriTech sector is an emerging technology sector using the Internet of Things (IoT), the latest innovations in coatings as well as data and relationships to accelerate the seizure of opportunities in the food and agricultural industries. Whether focusing on generating easily accessible information to make data-driven decisions in an orchard, or optimizing the value downstream by expanding the use of coatings to reduce food waste or using data and past relationships to attribute value to future sales, innovative startups in the space are playing a role in further refining applications of technology to add value to different stakeholders across the supply chain. The purpose of this research was to evaluate a selected number of these emerging Agritech products within the context of their ability to help their users create blue ocean strategies that shift the competitive advantage landscape in their industries. The selected technologies spanned use in field , moisture measurement, and financing. These solutions allow the customers to reduce their waste, maintain the quality of their production, optimize productivity, and increase their overall profitability. In providing these solutions, these companies separate themselves from their competitors. But they do more. They also alter the nature of competition in their industries because they, through their Blue Ocean Strategy actions, force their peers to up their game to serve their customers or else risk losing them. The three companies reviewed have each been around for at least a decade, and in that time some competitors have sprung up in the space, offering similar solutions in the past few years. However, one of the strongest advantages of being first to market for your product or service is that you can continue deploying Blue Ocean strategies to continue molding the market offering and in combination with relationship-building efforts, these evolutions can result in a dynamic, sustainable business that continuously adds value to the supply chain. They also alter the nature of competition in their industries because they, through their Blue Ocean Strategy actions, force their peers to up their game to serve their customers or else risk losing them.
Keywords: Blue Ocean; Agritech; Innovation; Financing; Weather station; Coating